How do social entrepreneurship factors influence sustainable business development? The mediating role of social network - Kusmantini, Titik; Sutiono, Heru Tri; Hartati, Anis Siti; Robani, Anidah; Diantoro, Aris Kusumo; Rahmadati, Ashila Metta (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study aimed to empirically investigate the factors of social entrepreneurship - namely, social mission, social innovation, and the mediating role of social networks in achieving sustainable business development within developing tourist villages. The research employed a quantitative approach, focusing on 42 tourist villages in Bantul Regency. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that social missions and social networks significantly and positively impact sustainable business development. However, social innovation did not show a significant effect on sustainable business development. Notably, social networks positively and significantly mediated the relationship between social innovation and sustainable business development. This study has several limitations. Firstly, it measured only two factors and one mediator of social entrepreneurship in addressing sustainable business development. Future research could explore other elements of social entrepreneurship, such as risk-taking. Secondly, social networking was used as a mediating variable; future studies could expand on this by incorporating HR practices. The results of this study have implications for social entrepreneurs, emphasizing the creation of relevant social and economic value for individuals and teams by addressing social and environmental needs. This approach is essential for developing creative and innovative solutions that ensure social, economic, and environmental sustainability in both normal and abnormal ecological situations.